Psychiatric morbidity among the patients with acne Vulgaris in a tertiary care Hospital - Ahmed, Fahmida; Husain, Anwar; Begum, Meherunnessa; Alam, Mohd Nurul; Ibrahim, Muhammad Ayaaz (Bangladesh Journal of Medical Science, 2019)
Background: Acne vulgaris is a chronic inflammatory skin disorder which has a high prevalence among adolescence and young adults. Although acne does not cause direct physical impairment, it can produce a significant psychosocial burden. As the face is almost always the site of involvement of acne, its presence can alter one’s perception of body image. Increased levels of anxiety, anger, depression, and frustration are also observed in patients with acne. Acne affects social, vocational, and academic performance of teenagers & young adult. Objective: To identify socio-demographic profile and to evaluate the psychiatric morbidity in patients with acne vulgaris in a tertiary care hospital. Materials and Methods: This cross sectional study was conducted from June 2017 to December 2017 among the patients of acne vulgaris attending outpatient department of Dermatology in Ibn Sina Medical College Hospital, Dhaka. Purposive sampling technique was used. The sample size of the study was 181. Data were collected by using semi structured socio-demographic questionnaire and the SRQ to screen psychiatric symptoms. The Self Reporting Questionnaire (SRQ), is a psychiatric case finding instrument, was developed by World Health Organization (WHO) to screen for psychiatric disturbance especially among developing countries. The data obtained was collected, tabulated and subjected to statistical analysis using the Statistical Package for Social Sciences (SPSS), for windows version 20. Results: Study was conducted on 181patients comprising 135(74.6%) were female & 46(25.4%) were male. Age group between 16 to 22 years carried maximum incidence 100(55.2%). Among the patients Psychiatric morbidity was found in86(48%) of the study population. Psychiatric morbidity was found more in young and females patients. Among the types of psychiatric morbidity Anxiety disorders were 57(66.3%) & Major Depressive Disorder(MDD) was 29(33.7%).Anxiety disorders were included social phobia (26.7%), generalized anxiety disorder (GAD) (18.6%), panic disorder (14%) and obsessive compulsive disorder (OCD)(7%). Conclusion: Patients with acne vulgaris in whom psychiatric morbidity is present, should be routinely evaluated and their psychiatric morbidity need to be treated adequately for maximize their health. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.773-778